Pancancer analysis of DNA damage repair gene mutations and their impact on immune regulatory gene expression - Kanchana Yadav; Trishala Das; Andrew M. Lynn (Scientific Reports)
Abstract DNA damage is a key factor in many human disorders, including cancer, chronic inflammation, and early aging. Genes involved in DNA damage repair (DDR) not only maintain genomic stability but also contribute to immune responses by regulating the expression of antimicrobial peptides and ligands that activate immune receptors. Various components of the DNA damage response (DDR), including DNA damage sensors, transducer kinases, and effector proteins, are capable of activating diverse immunological signaling pathways. While DDR gene mutations are common in cancers, their effects on immune characteristics are not well understood. We investigated how mutations in DDR genes influence the expression of immune regulatory genes, including immune stimulators, inhibitors, and genes related to the major histocompatibility complex (MHC) pathway. Using gene expression data from The Cancer Genome Atlas (TCGA) and mutation data from cBioPortal, we analyzed 264 DDR-related genes and 66 immune regulatory genes. These genes were clustered and categorized using Metascape, an integrative bioinformatics tool that applies enrichment-based analysis to group functionally related genes into clusters. The clustered genes were further validated through a literature review and the GeneCards database. We scored the change in immune regulatory gene expression in response to DDR gene mutations to identify differentially expressed immune stimulators, inhibitors, and MHC-related genes. Our analysis revealed positive and negative correlations between DDR gene mutations and the expression of immune modulators. These findings could help guide future cancer treatments based on biomarkers and immunotherapy strategies.